The Overlap between Fibromyalgia Syndrome and Myotonia Congenita - Nam, Tai-Seung (J Clin Neurol, 2015)
BACKGROUND: Fibromyalgia syndrome (FMS) is a complex disorder characterized by chronic widespread pain (CWP), multiple areas of tenderness, sleep disturbance, fatigue, and mood or cognitive dysfunction. Myotonia congenita (MC) is an inherited myopathic disorder that is caused by mutations in the gene encoding the skeletal muscle chloride channel, which can infrequently manifest as generalized muscle cramps or myalgia. CASE REPORT: The first case was a 33-year-old woman who complained of CWP and chronic headache occurring during pregnancy, and the second case was a 37-year-old man with CWP and depression who suffered from cold-induced muscle cramps. These two patients were initially diagnosed with FMS by rheumatologists, based on CWP of longer than 3 months duration and mechanical tenderness in specific body regions. However, these two FMS patients were subsequently also diagnosed with MC. CONCLUSIONS: These two cases are the first report of an overlap of CWP between FMS and MC.